Proton magnetic resonance spectroscopy as a monitoring tool for electroconvulsive therapy effects on the brain - Sartorius, Alexander; Henn, Fritz A.; Ende, Gabriele (Current psychiatry reviews, 2006)
Electroconvulsive therapy (ECT) is still the most effective treatment not only for psychotic depression, but also for treatment of resistant or other sever...